Methenamine hippurate to prevent recurrent urinary tract infections in older women: protocol for a randomised, placebo-controlled trial (ImpresU) - Cees M P M Hertogh; Anna Kowalczyk; Maciek Godycki-Cwirko; Morten Lindbaek; Ronny Gunnarsson; Pär-Daniel Sundvall; Theo J M Verheij; Nils Grude; Wim G Groen; Silje Rebekka Heltveit-Olsen; Sigurd Hoye; Egill Snaebjörnsson Arnljots; et al. (BMJ Open, 2022)
Introduction Methenamine hippurate is a urinary antiseptic used as preventive treatment for recurrent urinary tract infections (UTIs) in some Scandinavian countries. However, the scientific evidence for the preventive effect and safety for longer-term use is limited. The aim of this study is to assess whether methenamine hippurate can reduce the incidence of UTIs in older women with recurrent UTIs.Methods and analysis The ImpresU consortium is a collaboration between Norway, Sweden, Poland and the Netherlands. The study is a randomised, controlled, triple-blind phase IV clinical trial. Women ≥70 years with recurrent UTIs are screened for eligibility in a general practice setting. We aim to include 400 women in total, with 100 recruited from each collaborating country. The participants are randomised to treatment with methenamine hippurate 1 g or placebo tablets two times per day for a treatment period of 6 months, followed by a drug-free follow-up period of 6 months. The primary outcome is number of antibiotic treatments for UTIs during the treatment period. The secondary outcomes include number of antibiotic treatments for UTIs during the follow-up period and self-reported symptom of severity and duration of UTI episodes. Differences in complications between the treatment groups are measured as safety outcomes. We also aim to investigate whether strain characteristics or phylogenetic subgroups of Escherichia coli present in the urine culture at inclusion have a modifying effect on the outcomes.Ethics and dissemination Ethical approvals are obtained in all participating countries. The results will be communicated in peer-reviewed journals and at scientific conferences.Trial registration number ClinicalTrials.gov Registry (NCT04077580); EudraCT: 2018-002235-15.